PARTISIPASI POLITIK PEMILIH PEMULA DALAM PESTA DEMOKRASI - Azirah (Prodi Tata Negara (Siyasah) IAIN Langsa, 2019)
Beginner voters have different characteristics with older people in general. Beginner voters tend to be critical, self-contained, independent and are not satisfied with the establishment, pro-change and so on. The characteristics condusive to building a community of intelligent voters in the general election voters have rational consideration in determining his choice. For example, because the integrity of the political party leaders nominated, track record or work programs are offered. Because it has not had experience in presidential elections, beginner voters need to know and understand the various matters related to the election is held, what are the stages of the election, anyone who is eligible to participate in the elections, how the procedures for exercising the right to vote in elections and so on. The beginner voters expexted that still can maintain their political participation, so that when the quota rights of beginner voters can be run by continuing to participate at this stage then democracy will be able to bring the era of Indonesian democracy at this stage of the better later on, of course it would be better anyway when beginner voters can choose intelligently based sciences that have been obtained and supported with good ethics is also based on conscience and integrity in the absence of negative things from those who play with a sense of cheating.